Does Geographical Origin of Long-Tailed Macaques (Macaca fascicularis) Matter in Drug Safety Assessment?: A Literature Review and Proposed Conclusion. (July 2022) - Weinbauer, Gerhard; Mecklenburg, Lars
Long-tailed macaques are the predominant nonhuman primate species for the nonclinical safety testing of biopharmaceuticals. This species comprises 9 subspecies with Macaca fascicularis fascicularis naturally occurring in Southeast Asia. Since the 17th century, M. f. fascicularis also occurs on Mauritius. Cynomolgus macaques do not naturally occur in China, but are bred in many farms across the country. The current shortage in animal supply raises the question whether geographical animal origin matters and if animals from different geographical regions can be combined on a drug development program or even a single experiment. This article reviews geographical animal origin in relation to selected endpoints that are relevant in nonclinical drug safety testing. Animals from different countries within Asia mainland do not appear to show any meaningful difference. Very little data are available for animals from Asia island. Mauritian animals show consistent differences from Asian animals in several clinical and anatomical pathology parameters. For developmental parameters, animals from Mauritius and Asia are comparable with the exception that Mauritian animals mature faster. In the authors' view, differences between the geographical clusters can be accounted for as long as baseline and reference data are available.